THE RELATIONSHIP BETWEEN BASELINE CD4 T CELLS’ LEVEL AND RECOVERY RATE AFTER INITIATION OF ART IN HIV/AIDS INFECTED AT HOSPITAL FOR TROPICAL DISEASES, VIETNAM - PHU, TAO GIA; HONG NHUNG, HUYNH THI (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: HIV/AIDS pandemic continues to be a public health problem in developing countries. This study aimed to assess the correlation of recovery responses and baseline CD4 T cells’ level in HIV/AIDS adult patients after initiation of antiretroviral therapy (ART) in Vietnam. Methods: The study was a clinic-based longitudinal study done at an outpatient clinic, Tropical Diseases Hospital, Ho Chi Minh City, Vietnam, from 10/2018 to 8/2019. Results: Ninety-three patients were provided informed consent to participate in this study. Overall, the mean of CD4 T cell counts was 161.7 cells/μl. In AIDS patients groups, at the baseline mean of T CD4 cell was 65 cells/μl and in the non-AIDS group was 315 cells/μl. The slope of the plotted overall CD4 cell counts increased significantly in both two groups and the steepest increases in the first 3 months. After 6 months, patients who were AIDS stages were had a higher viral load in plasma than others, with p<0.005. The changes in CD4 T cell counts were significantly associated with age and occupational status. Conclusion: The present study found that immunological responses of patients with first-line ART were not related to baseline CD4 T cells’ level. However, low baseline CD4 counts were associated with poor virologic suppression.